The role of toxoplasma gondii (Tg) in schizophrenia: serofrequency and serointensity of Tg / Nor Fatini Adam - Adam, Nor Fatini (2015)
Infection with Toxoplasma gondii (Tg) in the central nervous system causes behavioural, personality changes and psychotic symptoms mimicking schizophrenia, a psychiatric illness with unknown aetiology. The aim of this study was to determine the seroprevalence, serointensity of Tg IgG, IgM antibodies and Tg DNA in patients with Schizophrenia and its relationship with demographic profile and clinical factors. This was a cross-sectional study examining the role of Tg in patients with Schizophrenia attending the Sg Buloh Hospital and University Malaya Medical Centre (UMMC) during a period from July 2010 to December 2012. A total of 156 subjects consisting of 57 patients with chronic Schizophrenia, 44 acute Schizophrenia and 55 healthy individuals participated in this study. The demographic profiles, risks and clinical factors were examined to determine the positivity and intensity of Tg IgG, IgM antibodies and Tg DNA. The seropositivity and serointensity of Tg antibodies were measured using Enzyme Linked Immunosorbent Assay (ELISA) while positivity and intensity Tg DNA were measured using Real Time PCR. The seropositivity of IgG antibody were significantly higher in all Schizophrenia, remission and acute Schizophrenia patients than control (p<0.001). The serointensity of IgG antibody were also significantly higher in all Schizophrenia, remission and acute Schizophrenia patients than control (p<0.05). The positivity of DNA Tg were also significantly higher in all Schizophrenia, remission and acute schizophrenia than control (p<0.05).The intensity of Tg DNA were also significantly higher in all Schizophrenia,remission and acute Schizophrenia patients than control (p<0.05). This study suggests that Tg has a significant role in Schizophrenia.